Effect of zinc supplementation on bone formation in hemodialysis patients with normal or low turnover bone. (10th September 2014) - Shiota, Jun; Tagawa, Hitoshi; Izumi, Naoki; Higashikawa, Shingo; Kasahara, Hitoshi
Abstract: Zinc (Zn) is an essential trace element, which has been shown to stimulate osteoblastic bone formation and to inhibit osteoclastic bone resorption in vitro . In thalassemia, major patients Zn supplementation was reported to increase whole-body bone mineral content and areal bone mineral density. Therefore, we investigated the effect of Zn supplementation on bone formation in hemodialysis (HD) patients. Nine male patients with age of 66 (35–78) years indicated by median (range), HD vintage of 57 (4–97) months and serum intact parathyroid hormone (PTH) of 113 (6–310) pg/mL were supplemented with polaprezinc containing 34 mg Zn/day for 18 months. Doses of vitamin D were not changed during supplementation. Blood was collected at baseline, 3, 6, 12 and 18 months. Serum Zn increased significantly from 58 (52–65) μg/dL to 71 (57–93) μg/dL at three months and remained unchanged until 18 months. No changes were observed in serum intact PTH during supplementation. Although we found no changes in serum bone alkaline phosphatase (BAP) during Zn supplementation analyzed by Friedman test and Scheffe post hoc test, a significant trend of increase in serum BAP was verified by Jonckheere–Terpstra test ( p =  0.0409). On the contrary, there was no trend in serum TRACP5b by Jonckheere–Terpstra test. Therefore, we suggested the effect of Zn supplementation on promoting bone formation, not affected by the status of PTH and vitamin D, in HD patients with normal or low turnover bone.